2020
DOI: 10.1175/bams-d-18-0302.1
|View full text |Cite
|
Sign up to set email alerts
|

The California Baseline Ozone Transport Study (CABOTS)

Abstract: Ozone is one of the six “criteria” pollutants identified by the U.S. Clean Air Act Amendment of 1970 as particularly harmful to human health. Concentrations have decreased markedly across the United States over the past 50 years in response to regulatory efforts, but continuing research on its deleterious effects have spurred further reductions in the legal threshold. The South Coast and San Joaquin Valley Air Basins of California remain the only two “extreme” ozone nonattainment areas in the United States. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 66 publications
(60 reference statements)
3
27
0
Order By: Relevance
“…Also, no reduction could be seen in the 1 • IAV time series plots over San Francisco and Los Angeles (Figure 5). The US west coast frequently experiences long-range trans-pacific transport events from Asia and Europe that result in increased pollutants' levels in this region [55,72], which also peaks in late spring, coinciding with the pandemic lockdown incidence. The increase or no change in NO 2 levels in San Francisco despite reduced NO 2 emissions from their large traffic volume demonstrates that other sources dominate, e.g., meteorology and pollution events [14,73].…”
Section: West Coastmentioning
confidence: 99%
“…Also, no reduction could be seen in the 1 • IAV time series plots over San Francisco and Los Angeles (Figure 5). The US west coast frequently experiences long-range trans-pacific transport events from Asia and Europe that result in increased pollutants' levels in this region [55,72], which also peaks in late spring, coinciding with the pandemic lockdown incidence. The increase or no change in NO 2 levels in San Francisco despite reduced NO 2 emissions from their large traffic volume demonstrates that other sources dominate, e.g., meteorology and pollution events [14,73].…”
Section: West Coastmentioning
confidence: 99%
“…Planning for the FAST-LVOS day-to-day activities and IOPs relied primarily on long range weather forecasts from the (Stein et al, 2015), and stratospheric, Asian pollution, and biomass burning tracers calculated using the FLEXPART particle dispersion model (Brioude et al, 2009;Brioude et al, 2007). The RAP-Chem and FLEXPART models were also used to support the 2016 CABOTS field campaign and are described elsewhere (Faloona et al, 2020). The FAST-LVOS measurements were also simulated by the GEOS-Chem and NOAA Geophysical Fluid Dynamics Laboratory (NOAA GFDL) AM4 chemistry-climate models; these efforts are described in the companion paper by Zhang et al ((Zhang et al, 2020).…”
Section: Model Supportmentioning
confidence: 99%
“…Previous airborne and ground-based lidar measurements have shown that elevated O3 layers are common features of the lower free troposphere between ~3 and 6 km a.s.l. above California (Langford et al, 2012;Ryerson et al, 2013;Faloona et al, 2020) and southern Nevada (Langford et al, 2015b;Langford et al, 2017) in late spring and early summer, and it is well established that the U.S. West Coast is one of the global hotspots for deep stratosphere-to-troposphere transport (STT) of O3 in springtime (Wernli and Bourqui, 2002;Sprenger and Wernli, 2003;James et al, 2003;Skerlak et al, 2014;Skerlak et al, 2015;Breeden et al, 2021). Deep STT refers to those intrusions that descend from the tropopause to 700 hPa in 5 days or less (Wernli and Bourqui, 2002;Sprenger and Wernli, 2003), and occurs primarily through the formation of tropopause folds, tongues of lower stratospheric air that descend isentropically beneath the jet stream circulating around upper-level lows.…”
Section: Introductionmentioning
confidence: 99%
“…The CABOTS field campaign (Faloona et al, 2020) was organized by the California Air Resources Board to investigate the contributions of background O 3 originating from Asian pollution (Lin, Fiore, Horowitz et al, 2012) and stratospheric intrusions (Lin, Fiore, Cooper et al, 2012) on surface concentrations in the SJVAB (Figure 1). The study was conducted between late May and mid‐August of 2016 with two intensive operating periods (IOP1: 27 May to 18 June and IOP2: 18 July to 7 August).…”
Section: The California Baseline Ozone Transport Studymentioning
confidence: 99%
“…In this paper, we use airborne, surface, and remote sensing measurements made during the 2016 California Baseline Ozone Transport Study (CABOTS) (Faloona et al, 2020) to examine the production of O 3 in the Soberanes Fire plume and estimate the impact on surface O 3 concentrations in the SJVAB during the summer of 2016. This fire, which burned more than 52,600 ha (130,000 acres) along the central California coast between 22 July and 12 October 2016, created an elevated smoke haze that covered the southern and central SJVAB in late July and early August.…”
Section: Introductionmentioning
confidence: 99%